Landscape and climate change. A resilient strategy for the adaption plan of the Ravenna area in Italy. - Lobosco,Gianni (2020)
Abstract The contribution presents the results of a research project carried out within the main framework of the “Sustainable Energy and Climate Action Plan” for the Ravenna Municipality, one of the signatories of the “Covenant of Mayors for Climate and Energy”. The project goal is to provide decision makers and city planners with landscape-oriented strategies capable of improving the territorial resilience vis-a-vis climate change impacts in the next decades. The research focuses on the construction of future alternative scenarios on a 2100 horizon. From their comparison, a short-term vision (2050) open to alternative developments has been designed. The study provides an overall view, on a municipal scale, of the main adaptation actions that can be implemented; then, it tests their potential effectiveness on smaller case-studies illustrating some recurring landscape units of the territory.